ENTER THE WORLD OF MICROBIOLOGY : INTERVIEWS ABOUT THE WORLD'S MOST FAMOUS MICROBIOLOGISTS - Varela, Manuel F., author; Shaughnessy, Michael F., author (Hauppauge, New York : Nova Science Publisher's, Inc., 2019)
Includes bibliographical references and index.